Microbiological evaluation of Colonial cheeses produced in Roque Gonzales, Northwest of Rio Grande do Sul state, Brazil - Daniel Daroit; Maiára Mates Ribas (Revista de Ciência Veterinária e Saúde Pública, 2022)
Colonial cheese, from both economic and cultural perspectives, in an important product manufactured from raw milk by rural families in southern Brazil. Since microbial contamination might negatively affect the food quality and safety, the aim of the present work was to evaluate the microbiological quality of eight Colonial cheeses manufactured in Roque Gonzales, northwest Rio Grande do Sul, Brazil. Total coliforms, considered as environmental contaminants, ranged from 1.5 × 102 to 2.3 × 105 Most Probable Number (MPN)/g. Enumeration of thermotolerant coliforms, used as sanitary indicators, ranged from <1.5 MPN/g to 1.5 × 104 MPN/g. According to the Brazilian legislation for high moisture cheeses, three Colonial cheeses presented nonconformity regarding total coliforms (>1 × 104 MPN/g), and one of these was inadequate for consumption due to thermotolerant coliform counts (>5 × 103 MPN/g). Aerobic mesophilic bacteria ranged from 107 to 109 Colony Forming Units (CFU)/g, and molds and yeasts were between 103 and 104 CFU/g. Mesophilic bacteria, and molds and yeasts, are indicators of environmental contamination, commonly leading to product deterioration. Results indicate unsatisfactory hygienic-sanitary conditions, suggesting the use of contaminated milk, deficiencies during production and/or improper handling. Considering the growing interest of consumers in Colonial cheeses, and also the importance of these cheeses for rural families, actions that promote hygienic practices in the production chain can benefit the quality and safety of these products.